IDENTIFIKASI KRITERIA EVALUASI PERANCANGAN RUANG PUBLIK TERPADU RAMAH ANAK (RPTRA) DKI JAKARTA - Tamiya Miftau Saada Kasman; Ita Roihanah (Universitas Mercu Buana, 2023)
One of the DKI Jakarta Provincial Government's programs, Child-Friendly Integrated Public Spaces (RPTRA), which began in 2015 has been successfully constructed in 324 places. This is the government's attempt to create kid-friendly public area amenities, which previously received little attention. However, as time goes by, several flaws are discovered, including design elements unsuitable for children, unkempt facilities, damaged play equipment, and uneven distribution of RPTRA locations. In 2016, the government has compiled regulation about Space Utilization in RPTRA. However, until now there are no guidelines for evaluating the RPTRA program which has been running for eight years. In order for RPTRAs to continue serving the requirements of the community and to be adequately maintained in accordance with public space standards that are ideal for children, mothers, the elderly, and people with disabilities, this study aims to establish the criteria that must be met in the RPTRA design. It is anticipated that based on the findings of the theoretical study, it will be possible to suggest several criteria for the development and design of the next RPTRA. The research methode is qualitative that involves gathering secondary data from both prior studies and theories concerning the design of public open space that children friendly, and the guidelines from UN Habitat. Then observations were also carried out at an RPTRA to see the condition of facilities that comply with government standart. From the identification, several criteria that must be considered when doing the evaluation, there are spatial and user aspects. Spacial analysis including accessibility, security, safety, facility, vegetation, and health. User characteristic and behavior in RPTRA including comfort, pleasure, and hospitality, are needed to evaluate the design of RPTRA.